Vesicle-Mediated Dendritic Cell Activation in Acinetobacter baumannii Clinical Isolate, which Contributes to Th2 Response - Wei Cai; Dinesh Kumar Kesavan; Jianjun Cheng; Aparna Vasudevan; Huixuan Wang; Jie Wan; Mohamed Hamed Abdelaziz; Zhaoliang Su; Shengjun Wang; Huaxi Xu (Journal of Immunology Research)
Acinetobacter baumannii, as a nonfermentation Gram-negative bacterium, mainly cause nosocomial infections in critically ill patients. With the widespread of multidrug-resistant Acinetobacter baumannii, the urgency of developing effective therapy options has been emphasized nowadays. Outer membrane vesicles derived from bacteria show potential vaccine effects against bacterial infection in recent study. Our present research is aimed at investigating the mechanisms involved in immune protection of mice after outer membrane vesicle immunization. As our data showed, the outer membrane vesicle from an Acinetobacter baumannii clinical strain could activate bone marrow-derived dendritic cells (BMDCs) to promote Th2 activity together with humoral immune responses to Acinetobacter baumannii-induced sepsis, which might enlighten people to have a better understanding of OMVs’ role as a vaccine to prevent bacterial infections.